Inducción de estructuras callogénicas en Cattleya maxima Lindl., a partir de explantes obtenidos de vitroplantas - Cárdenas Quevedo, Daniela Fernanda (2024)
As a species of plants, orchids have a significant ecological and economic importance, as they are used in forests and in the commercialization of flowers; however, they are subject to limitations when it comes to germination and establishment in natural environments. Cattleya maxima Lindl. is a highly demanded species due to the showiness and beauty of its flowers; it is included in Appendix II of CITES. Consequently, plant biotechnology contributes to the preservation of species of plant that are difficult to propagate and multiply in vitro through the application of in vivo culture techniques. Hence, the present research attempted to induce the formation of callogeneic structures in Cattleya maxima Lindl, in the culture medium of Knudson-C (KC-1946) and Murashige and Skoog (MS-1962), under different hormonal concentrations of auxin-cytokinin (2,4-D and BAP) and under total darkness conditions. The plant material used was obtained from vitroplants of the germplasm bank of the Plant Micropropagation Laboratory of the UNL. The variables evaluated were: percentage of contamination, percentage of phenolization, number of days to contamination, percentage of explants with callus, number of days to callus formation, percentage of roots, percentage of shoots, percentage of callus color and percentage of callus friability. A completely randomized experimental design was used, with eight treatments and three replications. In order to evaluate the variables, data was collected on a daily basis for 90 days. The results obtained show that contamination was present in the two culture media evaluated; thus, in KC, T2 obtained 13.33 % and in DM, T0 reached 20 % contamination. The percentage of phenolization recorded did not exceed 20 % in the two culture media, for KC at T5 and in MS at T6. There was a 100% callus formation rate in the KC culture medium in the T4 and T7 treatments, whereas the percentage in the MS culture medium was slightly lower across all treatments; thus, T7 reached 93.33%. The formation of callus structures in the KC culture medium began 28 days after inoculation and in MS callus formation began 19 days after inoculation. In the variable de novo root formation, no data were recorded in any of the treatments tested in the two culture media up to 90 days of evaluation. For callogenic structures with de novo shoots, T4 recorded 43.33 % of formation in the KC medium; however, in MS, this percentage decreased considerably; thus, only 10 % was observed in this same treatment. With respect to the color of the callus structures, in KC in the T4 treatment, 93.33 % of the explants were cream-colored, showing good callus condition; while in MS, T4 recorded 76.67 % of cream-colored structures. Accordingly, in DM, the callus formed had a much lower degree of friability than in KC. For example, in KC, treatments T4 and T5 both displayed 70 percent friable calli; in DM, treatment 5 T7 displayed 26.67 percent friability. It was concluded that the auxin-cytokinin hormonal balance of 10.0 mg L -1 2,4-D + 1,0 mg L-1 BAP (T7) proved to be effective in the formation of callogeneic structures in explants obtained from vitroplants of Cattleya maxima Lindl. in the two culture media (Knudson-C and Murashige and Skoog) with 100 % and 93.33 %, respectively.